1975
DOI: 10.1097/00000658-197507000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Gastric Rupture in the Newborn

Abstract: The term "spontaneous gastric rupture" is used to describe our cases of neonatal gastric perforation. Nineteen such neonates are reviewed. Current opinions regarding the possible etiology is included in the discussion. Neonatal asphyxia was the most commonly seen predisposing cause in our series (63%). Roentgenograms of the abdomen are most helpful in making a positive diagnosis. Surgical repair is the treatment of choice. All the surviving patients in our series underwent surgical repair. The need for gastros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Additionally, the mortality rate was not significantly different between different types of operations after 3 cases from the studies by Hwang et al due to the lack of surgical detail and 2, 1, and 2 cases from the studies by Wilson et al, Shashikumar et al, and Kiesewetter et al, respectively, were excluded because of death before surgery. [ 16 , 10 , 11 , 14 ] In this study, the higher mortality rate in preterm neonates and low birth weight neonates might be associated with the poor conditions of these subgroups that can easily develop sepsis and organ failure, eventually resulting in mortality. Furthermore, preterm and low birth weight neonates have a higher probability of ischemia episodes, such as hypotension and perinatal asphyxia, which may increase the risk of intestinal ischemia, thereby resulting in higher morbidity and mortality of gastric perforation.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Additionally, the mortality rate was not significantly different between different types of operations after 3 cases from the studies by Hwang et al due to the lack of surgical detail and 2, 1, and 2 cases from the studies by Wilson et al, Shashikumar et al, and Kiesewetter et al, respectively, were excluded because of death before surgery. [ 16 , 10 , 11 , 14 ] In this study, the higher mortality rate in preterm neonates and low birth weight neonates might be associated with the poor conditions of these subgroups that can easily develop sepsis and organ failure, eventually resulting in mortality. Furthermore, preterm and low birth weight neonates have a higher probability of ischemia episodes, such as hypotension and perinatal asphyxia, which may increase the risk of intestinal ischemia, thereby resulting in higher morbidity and mortality of gastric perforation.…”
Section: Discussionmentioning
confidence: 90%
“…[ 19 ] The perforation locations included the greater curvature (n = 90; 73.8%), lesser curvature (n = 16; 13.1%), anterior wall (n = 11; 9.0%), and posterior wall (n = 5; 4.1%) after 3, 1, and 42 cases from the studies by Shashikumar et al, Kiesewetter et al, and Sato et al were excluded, respectively, due to the unavailability of data on the location of perforation. [ 11 , 14 , 19 ] Three cases in study of Rosser et al and 1 case in study of Amadeo et al, which the perforation was identified at fundus, were included into group of greater curvature for statistical analysis-based anatomical position. [ 15 , 18 ] Furthermore, 18 cases from the studies by Houck et al and Rosser et al were excluded from survival analysis due to the lack of survival records in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important diagnostic sign of gastric perforation is pneumoperitoneum on a simple radiograph. Gastric perforation in the newborn occurs suddenly, and the characteristic saddlebag or football sign may be evident from the vast amount of intraperitoneal gas 8 16) . Immediate exploratory laparotomy is needed, and partial gastrectomy and primary closure is the standard of care depending on the area of necrotic tissues.…”
Section: Discussionmentioning
confidence: 99%